Methodological Approach of Environmental Experience Design to Enhancing Occupants’ Well-Being, Bangladesh - Sajal Chowdhury; Masa Noguchi; Hemanta Doloi (Buildings, 2023)
Bangladesh is an emerging nation that is urbanizing the fastest. Generally, middle-income families (as the main economic contributors) reside in high-density urban housing due to their socioeconomic disparities in Dhaka, Bangladesh, where physical design aspects focus on current housing sectors. The congested living situation worsens indoor environmental quality and has a negative impact on occupants’ mental well-being in their dwellings, resulting in a direct or indirect adverse effect on their productivity. Occupants’ living conditions can be improved by adjusting individual perceptions and experiences in their domestic environments. This study has developed an “Environmental Experience Design (EXD)” methodological approach that reflects a user-centered design theoretical framework. A field study on dwelling units (±1000 sq ft) conducted throughout the selected housings in Dhaka, Bangladesh, was carried out to examine occupants’ domestic experiences using semi-structured and structured interviews. After binary and thematic coding with significance, “Association Rules and Cluster Analysis” were used to ascertain relationships between three aspects (spatial, environmental, and user context) to explore and customize outcomes. This EXD methodological approach can be utilized to create an environmental (architectural) design solution that will enhance mental well-being by considering occupants’ needs and demands in household settings locally and worldwide.